Mining Companies Tax Avoidance Investigation by the Company Characteristics and CSR: Company Size as the Moderating Variable - Abdullah, Muhammad Wahyuddin; jupaing, Jupaing; Anwar, Puspita Hardianti; Hanafie, Hadriana (Jurnal Minds: Manajemen Ide dan Inspirasi, 2021)
This research aims to find the influence of capital intensity, sales growth, and CSR on tax avoidance and its strengthened impact on company size. The population in this study is all mining companies listed on the Indonesia Stock Exchange in 2014-2018. Determination of research samples based on purposive sampling method with a total of 85 data. Logistics regression analysis with MRA test with the strengthening company size. The results showed that capital intensity, sales growth, andCSRsignificantly positively affected tax avoidance. In addition, the results of this study also show that company size strengthens sales growth andCSRon tax avoidance with a significant favorable influence, and company size cannot strengthen capital intensity on tax avoidance.